Comparative Mitochondrial Genomic Analysis of Longhorn Beetles (Coleoptera: Chrysomeloidea) with Phylogenetic Implications - Yiming Niu; Fengming Shi; Xinyu Li; Sainan Zhang; Yabei Xu; Jing Tao; Meng Li; Yuxuan Zhao; Shixiang Zong (Arthropod Systematics & Phylogeny, 2024)
Longhorn beetles (Cerambycidae) play a vital role in global ecosystems. Some of them contribute to nutrient cycling and pollination, while others, pose a threat to forestry production. Despite their ecological importance, there has been a lack of comprehensive analyses on the mitochondrial genomes of Cerambycidae beetles. In this study, we have conducted mitochondrial genome sequencing and annotation for four Cerambycidae beetles: Monochamus sutor, Monochamus guerryi, Monochamus galloprovincialis, and Monochamus latefasciatus. Our analysis revealed a high degree of conservation in these mitochondrial genomes, with rare gene rearrangements observed across the Cerambycidae family. Additionally, a notable bias towards AT content was identified, with most genes using ATN as the start codon and TAA as the stop codon. Except for trnS1, all tRNA genes showed typical cloverleaf secondary structures. Phylogenetic analysis using IQ-TREE and Phylobayes consistently produced congruent topologies. At the gene level analyses, our results highlighted the remarkable conservation of the COX1 gene. Furthermore, at the species level, we observed strong adaptability in the Spondylidinae and Lepturinae subfamilies. We also offer our insights into contentious aspects of the phylogeny. Overall, our research contributes to a deeper understanding of the phylogeny and evolution of Cerambycidae, laying the groundwork for future population genetic investigations.